Kant contemporáneo / Kant subterráneo - Marey, Macarena (Con-Textos Kantianos. International Journal of Philosophy, 2021)
With this brief text I introduce the homonymous dossier. The idea of the dossier was to compile texts on matters that are not usually studied in the literature, written from original and polemical perspectives. These papers focus on subjects like the extraterrestrial perspective on humans (Laura Herrero Oliva), the a priori character of political conflict (Paola Romero), drinking alcohol with friends (Maria Borges) and political philosophy of the mind (Robert Hannah).